LANDASAN FILOSOFIS KEBIJAKAN PENGEMBANGAN KURIKULUM BAHASA ARAB - Tricahyo, Agus (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2013)
Curriculum is a component that takes an important role in the education system. Curriculum is formulated as the objectives that must be achieved so that the educational programs are able to run clearly and effectively. In addition, the curriculum provides an understanding of learning that ought to be owned by each student. The development of Arabic curriculum is an ongoing process that should always be conducted continuously. If it is not, the curriculum has become obsolete or outdated. Nevertheless, the curriculum development cannot be done with minimal effort or carelessly.The Arabic curriculum cannot be developed carelessly or improperly. In order to produce a qualified Arabic curriculum, it requires some substantial foundations, for instance the religious foundation, in which the purposes of Arabic education cannot be separated from the goal of understanding the study of Islam with its various science, philosophical, juridical, or linguistics; the differences laid on the way or technique in teaching the language influenced by different views on seeing the nature of language, analyzing and describing the language, psycholinguistics, sociolinguistics, and the foundation of science and technology. Hence, the curriculum should be able to accommodate and anticipate the pace of developments in science and technology.Â Ø¥Ù Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙ Ø¯ÙØ±Ù Ø§ÙÙØ§Ù ÙÙ Ø§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ. ÙØ¶Ø¹ Ø§ÙÙÙÙØ¬ ÙÙÙÙ Ø§ÙØ£ÙØ¯Ø§Ù Ø§ÙÙØ±Ø¬ÙØ© ØØªÙ ØªÙÙÙ Ø§ÙØ®Ø·Ø© ÙÙØ³ÙØ± Ø§ÙØªØ±Ø¨ÙØ©Â  ÙØ§Ø¶ØØ© ÙØªØ¬ÙØ©.ÙØ¨Ø¬Ø§ÙØ¨ Ø°ÙÙØ Ø£Ø¹Ø·Ù Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù Ø§ÙÙÙÙ Ø¹Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙØ§Ø¬Ø¨ Ø§ÙØªÙØ§ÙÙ ÙÙØ·Ø§ÙØ¨. ÙØªÙÙÙØ© Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© ÙÙ Ø¹ÙÙÙØ© ÙØªÙØ§ØµÙØ© ÙØ§Ø¨Ø¯ ÙÙ Ø§ÙÙÙØ§Ù Ø¨ÙØ§Ø ÙØ¥ÙØ§ ÙØ³ÙÙÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙØªØ®ÙÙØ§. ÙÙÙÙ ÙØ§ÙÙÙÙ Ø£Ù ÙÙÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù Ø§Ø±ØªØ¬Ø§ÙÙØ§ Ø¯ÙÙ Ø¯Ø±Ø§Ø³Ø© Ø³Ø¨ÙØªÙ. ÙÙÙØØµÙÙ Ø¹ÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù Ø§ÙØ¬ÙØ¯ ÙØ§Ø¨Ø¯ ÙÙ Ø§ÙØ§Ø¹ØªÙØ§Ø¯ Ø¹ÙÙ Ø£Ø³Ø³ ÙÙÙØ©Ø ÙÙÙØ§ : Ø§ÙØ£Ø³Ø§Ø³ Ø§ÙØ¯ÙÙÙØ Ø£Ù Ø£Ù ØªØ±Ø¨ÙØ© Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© ÙØ§ØªÙÙØµÙ Ø¹Ù Ø§ÙÙØ¯Ù ÙÙÙÙ ÙØµØ§Ø¯Ø± ØªØ¹Ø§ÙÙÙ Ø§ÙØ¥Ø³ÙØ§Ù ÙØ¹ÙÙÙÙ Ø§ÙÙÙØ³ÙÙØ©Ø ÙØ§ÙÙØ¶Ø§Ø¦ÙØ©Ø ÙØ§ÙÙØºÙÙØ©. ÙÙØ¹ÙÙ Ø¨ÙØ°Ø§ Ø§ÙÙØ±Ù ÙÙ ÙÙÙÙØ© ØªØ¯Ø±ÙØ³ Ø§ÙÙØºØ© ÙØªØ£Ø«Ø±Ø© Ø¨Ø§ÙÙØ±Ù ÙÙ Ø§ÙÙØ¸Ø± Ø¥ÙÙ ØÙÙÙØ© Ø§ÙÙØºØ© ÙØ§ÙÙØ±Ù ÙÙ ÙÙÙÙØ© Ø§ÙØªØÙÙÙ ÙØªØµÙÙØ± Ø§ÙÙØºØ©Ø Ø¹ÙÙ Ø§ÙÙØºØ© Ø§ÙÙÙØ³ÙØ ÙØ¹ÙÙ Ø§ÙÙØºØ© Ø§ÙØ¥Ø¬ØªÙØ§Ø¹Ù ÙØ§ÙØ£Ø³Ø§Ø³ Ø§ÙÙØ¹Ø±ÙÙ ÙØ§ÙØªÙÙÙØ©. ÙÙØ±Ø¬Ù Ø£Ù ÙÙÙÙ Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³Ù ÙØªØ®Ø°Ø§ ÙÙØªØ®ÙÙØ§ ÙØªÙØ¯Ù Ø§ÙØ¹ÙÙÙ ÙØ§ÙØªÙÙÙØ©.